Hubungan Antara Kepemimpinan Kepala Sekolah Dan Komitmen Organisasi Dengan Kepuasan Kerja Guru Di Sekolah Menengah Atas (SMA) - Abadi, Hadi Prana; Annur, Aan Fadia (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Abstract: This study looked at the connection between job satisfaction and teacher organizational commitment and school leadership at a senior high school (SMA) in South Tangerang City. Quantitative correlational research is the research approach used here. Data were gathered using a questionnaire that was constructed using different variable indicators. A sample of 115 teachers was selected using the Slovin formula from a total of 161 populations across 5 secondary schools. The significance level for testing the null hypothesis, according to SPSS data analysis, is 0.05, and the resulting t number is higher than the t table. The principal's leadership factor, which accounts for 21.69% of the variation in job satisfaction, and organizational commitment, which accounts for 16.45%, are both revealed by the correlation coefficient data analysis. The level of job satisfaction is influenced by the client's organizational commitment and leadership abilities. The data gathered at Senior High School (SMA) South Tangerang City reveals a significant correlation between organizational engagement, principal leadership, and teacher job satisfaction.Keywords: Organizational Commitment; Principal leadership; Teacher Job Satisfaction Abstrak: Penelitian ini melihat hubungan antara kepuasan kerja dengan komitmen organisasi guru dan kepemimpinan sekolah pada Sekolah Menengah Atas (SMA) di Kota Tangerang Selatan. Penelitian kuantitatif korelasional adalah pendekatan penelitian yang digunakan disini. Data dikumpulkan dengan menggunakan kuesioner yang dibangun dengan menggunakan indikator variabel yang berbeda. Sampel 115 guru dipilih menggunakan rumus Slovin dari total 161 populasi di 5 sekolah menengah. Tingkat signifikansi pengujian hipotesis nol menurut analisis data SPSS adalah 0,05, dan angka t yang dihasilkan lebih besar dari t tabel. Faktor kepemimpinan kepala sekolah, yang menyumbang 21,69% dari variasi kepuasan kerja, dan komitmen organisasi, yang menyumbang 16,45%, keduanya diungkapkan oleh analisis data koefisien korelasi. Tingkat kepuasan kerja dipengaruhi oleh komitmen organisasi dan kemampuan kepemimpinan klien. Data yang dikumpulkan di Sekolah Menengah Atas (SMA) Kota Tangerang Selatan menunjukkan adanya hubungan yang signifikan antara keterikatan organisasi, kepemimpinan kepala sekolah, dan kepuasan kerja guru.Kata kunci: Komitmen Organisasi; Kepemimpinan Kepala Sekolah; Kepuasan Kerja Guru